Views from Addis Ababa. (2021) - Negm, Namira
Abstract : Adaptation is the one thing that the COVID-19 pandemic taught us. Not only as human beings in our personal lives but also as professionals working in multilateral diplomacy. We learned the hard way to adapt to a new reality of continuous lockdowns, working from home, conducting meetings virtually, and possible negotiations of legal instruments online. Simply, with all the challenges we met and despite the slow mode, multilateralism is still functioning and business is continuing.